ErbB3 is involved in activation of phosphatidylinositol 3-kinase by epidermal growth factor. - Soltoff, S P (1994)
Conflicting results concerning the ability of the epidermal growth factor (EGF) receptor to associate with and/or activate phosphatidylinositol (PtdIns) 3-kinase have been published. Despite the ability of EGF to stimulate the production of PtdIns 3-kinase products and to cause the appearance of PtdIns 3-kinase activity in antiphosphotyrosine immunoprecipitates in several cell lines, we did not detect EGF-stimulated PtdIns 3-kinase activity in anti-EGF receptor immunoprecipitates. This result is consistent with the lack of a phosphorylated Tyr-X-X-Met motif, the p85 Src homology 2 (SH2) domain recognition sequence, in this receptor sequence. The EGF receptor homolog, ErbB2 protein, also lacks this motif. However, the ErbB3 protein has seven repeats of the Tyr-X-X-Met motif in the carboxy-terminal unique domain. Here we show that in A431 cells, which express both the EGF receptor and ErbB3, PtdIns 3-kinase coprecipitates with the ErbB3 protein (p180erbB3) in response to EGF. p180erbB3 is also shown to be tyrosine phosphorylated in response to EGF. In contrast, a different mechanism for the activation of PtdIns 3-kinase in response to EGF occurs in certain cells (PC12 and A549 cells). Thus, we show for the first time that ErbB3 can mediate EGF responses in cells expressing both ErbB3 and the EGF receptor.